Results of Surgical and Nonsurgical Treatment of Aneurysms in a Developing Country - Kavian Ghandehari; Fahimeh Ahmadi; Azadeh Afzalnia (Stroke Research and Treatment)
Background. The impact of invasive methods of treatment on results in developing countries may differ from that in developed countries. Methods. This is a prospective clinical study of consecutive patients with Subarachnoid Haemorrhage (SAH) admitted to the Ghaem Hospital, Mashhad during the period from 2005 to 2009. The initial diagnosis and investigations were carried out by neurologists. The patients were divided into two groups. One received surgical treatment whilst the other group was managed medically. The decision as to the choice of the method of treatment was made by the neurosurgeons. The initial medical treatment was standardised for all the patients. The rate of complications and mortality was compared in both medical and surgical groups. Results. 120 SAH patients (52% females) with a mean age of 50.6 ± 7 years were evaluated. The angiography revealed the presence of an aneurysm in 62 patients. 63.5% of the patients received medical treatment and 37.5% underwent aneurysmal surgery. Difference of rebleeding rate in the two therapeutic groups was not significant; 𝑋2=.014, 𝑃=.91. The effect of rebleeding on mortality was not significant; 𝑋2=2.54, 𝑃=.14. Within 62 SAH patients with cerebral aneurysm, the mortality rate in both therapeutic groups was also not significantly different; 𝑋2=.16, 𝑃=.77. Conclusion. There is no significant difference in the mortality rate between the “surgical” and non-“surgical” groups of Iranian patients with SAH. This could be due to delay in performance of surgery in Iranian neurovascular centers.